2022
DOI: 10.3390/ijms23147595
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Theaflavins on Metabolic Syndrome: From Molecular Evidence to Gut Microbiome

Abstract: In recent years, many natural foods and herbs rich in phytochemicals have been proposed as health supplements for patients with metabolic syndrome (MetS). Theaflavins (TFs) are a polyphenol hydroxyl substance with the structure of diphenol ketone, and they have the potential to prevent and treat a wide range of MetS. However, the stability and bioavailability of TFs are poor. TFs have the marvelous ability to alleviate MetS through antiobesity and lipid-lowering (AMPK-FoxO3A-MnSOD, PPAR, AMPK, PI3K/Akt), hypog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…To assess the influence of 35e on mitochondrial function, an in vitro study employing liver HepG2/C3A human cells was performed (Shi et al., 2022). The study examined mitochondrial protein (carnitine palmitoyltransferase I [CPT‐I], carnitine palmitoyltransferase II [CPT‐II], heat shock protein 60 [HSP60], and translocase of the outer mitochondrial membrane 20 [Tom20]) expression within HepG2/C3A cells following a 6‐h treatment with three concentration gradients of 35e .…”
Section: Resultsmentioning
confidence: 99%
“…To assess the influence of 35e on mitochondrial function, an in vitro study employing liver HepG2/C3A human cells was performed (Shi et al., 2022). The study examined mitochondrial protein (carnitine palmitoyltransferase I [CPT‐I], carnitine palmitoyltransferase II [CPT‐II], heat shock protein 60 [HSP60], and translocase of the outer mitochondrial membrane 20 [Tom20]) expression within HepG2/C3A cells following a 6‐h treatment with three concentration gradients of 35e .…”
Section: Resultsmentioning
confidence: 99%
“…A recent review investigated the potential benefits of theaflavins, found in red wine, on metabolic syndrome, with a focus on the gut microbiome. It was discussed that theaflavins have the potential to positively impact the gut microbiota by increasing the abundance of beneficial gut bacteria such as Lachnoclostridium and Bifidobacterium 54 …”
Section: Methodsmentioning
confidence: 99%
“…It was discussed that theaflavins have the potential to positively impact the gut microbiota by increasing the abundance of beneficial gut bacteria such as Lachnoclostridium and Bifidobacterium. 54 A diet rich in proteins was shown to have a negative impact on health and is associated with increased mortality. 55 In a randomized clinical trial, patients with MetS received caloric restriction or isocaloric dietary protein restriction; both interventions resulted in positive metabolic outcomes such as weight loss, improved insulin sensitivity, blood glucose, lipid and blood pressure without any significant changes in the microbiome, suggesting that dietary metabolic health may only be indirectly related to the microbiome.…”
Section: Specialized Dietsmentioning
confidence: 99%
“…Polyphenols, due to their antioxidant, anti-platelet, and anti-inflammatory properties, can prevent or reduce the symptoms of various metabolic diseases, such as metabolic syndrome (which includes type 2 diabetes mellitus, central and abdominal obesity, systemic hypertension, and atherogenic dyslipidaemia) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], as well as cardiovascular diseases (e.g., atherosclerosis, myocardial infarction, heart failure, and stroke) [ 57 , 58 , 59 , 60 , 61 ]. Polyphenols inhibit LDL oxidation and increase HDL, improving endothelial function [ 62 ], reduce blood pressure [ 63 ], and improve the glucose homeostasis [ 64 ].…”
Section: Polyphenols In Disease Prevention and Treatmentmentioning
confidence: 99%